Association of Hypertension and Related Factors with Cognitive Performance in an Elderly Population (Bangladesh Journal of Medical Biochemistry, 2025)
This cross-sectional, analytical study to see the association of hypertension and its related factors with the cognitive performance of elderly people in an urban setting in Dhaka, Bangladesh, was conducted between January and December of 2016. A convenient sampling technique was adopted. A total of 189 elderly people (118 male and 71 female) were included in the study. A semi-structured questionnaire was first developed in English and then translated into Bangla. The questionnaire contained questions related to socio-demographic characteristics of the participants and their cognitive functions, as determined by using Mini Mental state Examination (MMSE), hypertension-related information including its medication, any comorbidities, e.g., diabetes mellitus, and family history. Socio-demographic data were analyzed with descriptive statistics. Chi-square test was applied to assess association of qualitative data. The age of the respondents ranged from 60 to 90 years. The mean age was 67.8±6.26 years. Higher proportion of male (37.3%) and female participants (36.6%) were in 60-64 years age group, while the lower proportion in ≥75 years age group (male 12.7% and female 14.1%). Strong associations were observed between hypertension and cognitive performance as well as between intake of prescribed anti-hypertensive drugs and cognitive performance (p0.05). Among different anti-hypertensive drugs users, only patients having calcium channel blockers showed association with their cognitive performance (p